OPPORTUNITIES FOR MODELING BUILDING MATERIALS AND STRUCTURES IN 3D DRAWINGS: ENHANCING CONSTRUCTION DESIGN AND ANALYSIS - Yusubjonov Jonibek Farkhod ugli (Ecomind Press, 2025)
Three-dimensional (3D) modeling of building materials and structural elements has become a cornerstone of modern construction design, allowing architects, engineers, and designers to visualize, analyze, and optimize complex structures with high precision. This study explores the opportunities offered by 3D modeling technologies for representing building materials, structural components, and entire constructions, emphasizing visualization, structural analysis, and material behavior simulation. Using the IMRaD structure, the research integrates literature review, case studies of 3D modeling applications, and experimental modeling using CAD and BIM platforms. Results indicate that 3D modeling enhances design accuracy, facilitates interdisciplinary collaboration, improves material optimization, and supports construction planning. The discussion addresses methodological considerations, software integration, and educational implications for training construction professionals. The conclusion underscores the significance of 3D modeling technologies in improving construction efficiency, reducing errors, and supporting innovative design practices.
Keywords: 3D Modeling, Building Materials, Structural Design, CAD, BIM, Construction Engineering, Visualization, Simulation.